Hubungan Profil Darah Lengkap dengan Hasil Tes Cepat Molekuler (TCM) Pasien Terduga Tuberculosis - Anisyah, Anisyah; Pauzan, Pauzan; Sukmana, Dhika Juliana (JSN : Jurnal Sains Natural, 2024)
Tuberculosis is a contagious infectious disease caused by mycobacterium tuberculosis which generally attacks the lungs in humans. This disease is transmitted by positive BTA sufferers and spreads through droplet nuclei when the sufferer coughs or sneezes. Bacteria that spread in the air can be transmitted by healthy people and can cause infection. The aim of this study was to determine the relationship between complete blood profiles and the results of rapid molecular test in patients suspected of having tuberculosis. This type of research uses analytical observational with a cross- sectional design. This study used secondary data from medical records of tuberculosis patients at the NTB Provincial Regional Hospitals. The collected data from complete blood examination results and molecular rapid tests are processed and presented in tabular form. The processed data was then analyzed statistically using SPSS with the chi-square test. Based on the results of research regarding the relationship between complete blood profiles and the results of the rapid molecular test for suspected tuberculosis patients at the NTB Provincial Regional Hospital, when examining leukocytes, erythrocytes, and platelets the p-value or sig. was obtained > 0,05, namely there is no significant relationship between the two variabels. Meanwhile, for hemoglobin, the P-Value was < 0,05, namely that there was a significant relationship between the two variabels